Impact of Conflict on Teaching Learning Process in Schools - Thapa, Tara Bahadur (Academic Voices: A Multidisciplinary Journal, 2016)
Conflict is abundantly present in every society. The nature and types of conflicts that emerge in school vary from school to school. The common types of conflicts usually occur between the students on one hand and school authority on the other. Other forms of conflicts include intrapersonal conflict among teachers as well as students regarding the causes of different norms and values, desires and selfishness. If conflicts are not resolved in time, they have destructive impacts in teaching learning, and it may lead to violence. This article highlights the causes of conflicts among students and teachers and its effects on teaching learning process in school. Academic Voices Vol.5 2015: 73-78